Exploring the relationship between green innovation on organizational performance with mediating roles of innovation orientation at SME’s manufacturing companies in Selangor: a conceptual paper - Ahmad Bakarim, Nur Aisya Addina; Abdul Rahim, Ramita; Hamzah, Muhammad Iskandar (Universiti Teknologi Mara Selangor, 2024)
This study explores the relationship between green innovation on organizational performance of Malaysian Small and Medium Enterprises (SMEs), particularly in Selangor. Green innovation is a method for resolving environmental concerns, promoting sustainability, and accelerating technological progress. It opens the path for a more sustainable and economically viable future. Besides, green innovation practices can assist organization in improving their performance by encouraging them to develop solutions that allow them to use less resources, reduce the likelihood of harm, and generate a carbon footprint within the firm. Previous research revealed that green innovation and organizational performance were positively related. However, these researches did not go further into the relationship between these constructs among manufacturing SMEs in Selangor. Therefore, the purpose of this study is to explore the green innovation on organizational performance among SMEs manufacturing companies in Selangor, Malaysia. This study conducted a purposive sampling survey of SMEs located in the Selangor, Malaysia. Self-administered questionnaires will be disseminated, and the data obtained will be analyzed using the partial least squares (SmartPLS) technique. The findings are expected to address the particular difficulties and possibilities that SMEs in Malaysia confront, which are critical to their long-term growth and competitiveness in both domestic and global markets. The research's personalized strategy attempts to improve these organizations' strategic capabilities by encouraging innovation, efficiency, and resilience. Therefore, developing a bespoke framework based on these insights could lead to more effective policies and support mechanisms, hence promoting Malaysia's economic progress and prosperity.